Developing A Mindfulness Module Using A Pocketbook to Improve Digital Self-Control in Students - Khoirunnisa, Firdaus; Eva, Nur; Muntaz, Khansa Salsabila (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to develop a pocketbook-based mindfulness module as an intervention to improve digital self-control among university students. The research employed a Research and Development (R&D) design, utilizing the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The development process included needs analysis, material design, instructional preparation, and validation by media and content experts. Validation results indicated that the module was feasible and rated from good to very good in terms of content, presentation, and appearance. The implementation of the module demonstrated improvements in students’ ability to manage digital use more consciously, purposefully, and adaptively. These findings highlight that the pocketbook-based mindfulness module is a relevant, practical, and effective intervention to support students in addressing the challenges of technology use in the digital era.